2017
DOI: 10.1149/2.0251711jss
|View full text |Cite
|
Sign up to set email alerts
|

Improved Linearity in AlGaN/GaN HEMTs for Millimeter-Wave Applications by Using Dual-Gate Fabrication

Abstract: An effective method of improving the linearity of AlGaN/GaN HEMTs by using dual-gate technology is demonstrated. In this letter, we compare the DC characteristics and device linearity of the dual-gate AlGaN/GaN HEMTs with conventional single-gate AlGaN/GaN HEMTs. The correlation between the extrinsic transconductance (G m ) with third-order intermodulation distortion (IM3) and third order intercept point (IP3) suggests that the broader G m distribution as a function of gate-bias, causes a lower IM3 level and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Guidry et al [127] demonstrated a N-polar metal insulator semiconductor (MIS) HEMT with a deep recess gate having OIP3/P DC of 11.4 dB at 30 GHz. In addition, Shrestha et al [128] proposed a N-polar GaN MIS-HEMT simultaneously to achieve a high linearity (OIP3/P DC of 15 dB) and a high gain (12.7 dB) at 30 GHz. Some special structures were also proposed to improve the linearity of the device.…”
Section: Othersmentioning
confidence: 99%
“…Guidry et al [127] demonstrated a N-polar metal insulator semiconductor (MIS) HEMT with a deep recess gate having OIP3/P DC of 11.4 dB at 30 GHz. In addition, Shrestha et al [128] proposed a N-polar GaN MIS-HEMT simultaneously to achieve a high linearity (OIP3/P DC of 15 dB) and a high gain (12.7 dB) at 30 GHz. Some special structures were also proposed to improve the linearity of the device.…”
Section: Othersmentioning
confidence: 99%
“…When it comes to improving the linearity of a HEMT device at very high frequency, i.e., the Ka band, the gate controllability performance, such as the and flatness of the device, becomes the critical factor for the improvement of the device’s linearity characteristics, such as the third-order output intercept point (OIP3) and third-order intermodulation output power (IMD3) [ 19 ]. A low second derivative value of the curve, meaning a flat curve, is favorable for the RF HEMT device to show that the device can withstand the gate voltage swing under high RF input power, keeping the device’s high switching capability as stable as possible [ 20 ]. Researchers have shown that better gate controllability could be achieved by etching AlGaN/GaN device gates along the gate width to form fin-shaped gates, overcoming the deficiencies of small gate length GaN devices, which have exhibited poor gate control over the 2DEG channel [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to mention that several ways have been proposed to overcome the limitations of the poor linearity for GaN HEMTs, such as dual-gate HEMTs [5][6][7], doublechannel structure [8][9][10], δ-doping layer [11][12][13], transitionalrecessed-gate technology [14], polarization doping field effect transistors (PolFETs) [15][16][17][18], and GaN FinFETs [19,20]. Apart from that, the reported graded-channel HEMTs also possess a wider and flatter transconductance [21][22][23].…”
Section: Introductionmentioning
confidence: 99%